New means of hydrogen storage – the potentials of methanol as energy storage for excessive windpower in North Germany - Gulden Johannes; Sklarow Andreas; Luschtinetz Thomas (E3S Web of Conferences, 2018)
The aim of the presented project is the technological development of hydrogen storage in methanol. This technology enables the carbon dioxide-based chemical storage of renewable energies as well as a decentralized supply of energy and hydrogen. Additional advantages are the very good compatibility with the existing infrastructure for liquid energy storage as well as the temporal decoupling of energy production and consumption. The latter can be managed independently, thus taking into account the fluctuating nature of wind and solar energy. The centrepiece is the use of new catalysts and processes that enable the chemical reactions in the methanol cycle under mild conditions.